The Gamification of Citizens' Participation in Policymaking - Masser, Kai (Springer International Publishing, 2018)
This book examines the use of game elements to encourage citizens to participate in political decision-making and the planning of large-scale public sector projects. It argues that success is based on a personal concern with the project and a belief in the influence on political decision making, but also on fun. Without fun, only a very small group of the 'usual suspects' will participate, especially in classic policymaking approaches like citizens' panels which require time and physical attendance. The book also examines the relationship between representative democracy and citizen participation from the perspective of direct democratic instruments in Germany. Readers from different countries with different political systems can decide for themselves, if and how the results from Germany are transferable to their respective conditions. Grounded in theoretical literature and statistical data, the book also makes use of narratives, applying a 'storytelling' approach to the case studies. Kai Masser is Senior Researcher at the German Research Institute for Public Administration (GRIP) and a Lecturer at the German University of Administrative Sciences, Speyer, Germany. Linda Mory is a Senior Project Consultant at a global IT company and a Lecturer at the German University of Administrative Sciences, Speyer, Germany. .